ENTREPRENEURSHIP PADA USAHA MIKRO, KECIL DAN MENENGAH (UMKM) - Satria, Rd. Okky (Majalah Bisnis & IPTEK, 2021)
SME development is a challenge for Indonesia to increase the role and contribution to national development. The need for planning strategies based on consideration of accelerating changes in the organizational environment that will lead to uncertainty within the organization. By reviewing more about the growth of the SME sector is expected to obtain new models in developing number Entrepreuner in Indonesia. Keywords: entrepreneurship; sme’s